MODERN POSSIBILITIES FOR DIAGNOSING AND TREATING CHRONIC CERVICITIS - Андреева, Маргарита Викторовна; Рамазанова, Мадина Расуловна; Заболотнева, Ксения Олеговна (Mother and Baby in Kuzbass, 2024)
A review of the literature on methods for diagnosing chronic cervicitis was conducted. The purpose of the work is to conduct a systematic analysis of literature data on modern diagnostic capabilities and tactics for managing patients with chronic cervicitis (CC). Materials and methods. The analysis was carried out based on the results of clinical, colposcopic, morphological, immunohistochemical and molecular genetic research methods. Results. The analysis of domestic and foreign literature showed that the use of modern methods of diagnosis and therapy will avoid chronicity of the process, complications, overdiagnosis of the degree of damage to the cervix and unnecessary invasive interventions.